2004
DOI: 10.1074/jbc.m308533200
|View full text |Cite
|
Sign up to set email alerts
|

The Hippocampal Cholinergic Neurostimulating Peptide, the N-terminal Fragment of the Secreted Phosphatidylethanolamine-binding Protein, Possesses a New Biological Activity on Cardiac Physiology

Abstract: Phosphatidylethanolamine-binding protein (PEBP), alternatively named Raf-1 kinase inhibitor protein, is the precursor of the hippocampal cholinergic neurostimulating peptide (HCNP) corresponding to its natural N-terminal fragment, previously described to be released by hippocampal neurons. PEBP is a soluble cytoplasmic protein, also associated with plasma and reticulum membranes of numerous cell types. In the present report, using biochemistry and cell biology techniques, we report for the first time the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 64 publications
1
56
0
Order By: Relevance
“…It has been suggested that RKIP-1 protein is a precursor of HCNP [29,30,37]. The reporter expression pattern in the mouse brain is consistent with potential endocrine relevance of the gene [1,15]. However, the mutation used herein does not disrupt exon I, preserving the N-terminal HCNP sequence for processing and function.…”
Section: Discussionmentioning
confidence: 65%
“…It has been suggested that RKIP-1 protein is a precursor of HCNP [29,30,37]. The reporter expression pattern in the mouse brain is consistent with potential endocrine relevance of the gene [1,15]. However, the mutation used herein does not disrupt exon I, preserving the N-terminal HCNP sequence for processing and function.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, PEPB expression has been detected on Western blots of heart and liver extracts (Frayne et al, 1999). Recently, an estimation of PEBP concentration in bovine serum, obtained after protein sequencing, indicated a value of 35 nM (Goumon et al, 2004). More recently, using chromaffin cells from bovine adrenal medulla as a well characterized secretion model, we demonstrated that PEBP and HCNP are present in chromaffin cells (intragranular matrix), from which they are secreted into the circulation with catecholamines (Goumon et al, 2004).…”
mentioning
confidence: 98%
“…56 In the brain, an N-terminal fragment of PEBP known as the "hippocampal cholinergic neurostimulating peptide" (HCNP) seems to serve as a transmitter and an endocrine factor. 57 PEBP is primarily a cytosolic protein, but is able to bind to cellular and model membranes through its N-and C-terminal ends. 58 In addition, a cavity at the protein surface binds phosphatidylethanolamine (PE) with high affinity; 58 this site can also bind other phospholipids (albeit with lower affinity) or opioids.…”
Section: Table 1 Autophagosomally Enriched Membrane-associated Proteinsmentioning
confidence: 99%